(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Brysina T. B., Vlasenko I. M. Developing the metaphorical thinking among students majoring in choreography in the process of working on etudes. The article deals with the process of metaphorical thinking development as a part of polyart education at higher schools. The article focuses on reasonability of studying etudes through such methods as special and choreographic, theatrical and acting as well as the methods of dramatic art. The authors suggest the algorithm of work on etudes, which promotes reasonable composition of a choreographic metaphor.